Redox Regulation of PTEN by Peroxiredoxins - Thang Nguyen Huu; Jiyoung Park; Ying Zhang; Iha Park; Hyun Joong Yoon; Hyun Ae Woo; Seung-Rock Lee (MDPI AG, 2021)
Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is known as a tumor suppressor gene that is frequently mutated in numerous human cancers and inherited syndromes. PTEN functions as a negative regulator of PI3K/Akt signaling pathway by dephosphorylating phosphatidylinositol (3, 4, 5)-trisphosphate (PIP3) to phosphatidylinositol (4, 5)-bisphosphate (PIP2), which leads to the inhibition of cell growth, proliferation, cell survival, and protein synthesis. PTEN contains a cysteine residue in the active site that can be oxidized by peroxides, forming an intramolecular disulfide bond between Cys124 and Cys71. Redox regulation of PTEN by reactive oxygen species (ROS) plays a crucial role in cellular signaling. Peroxiredoxins (Prxs) are a superfamily of peroxidase that catalyzes reduction of peroxides and maintains redox homeostasis. Mammalian Prxs have 6 isoforms (I-VI) and can scavenge cellular peroxides. It has been demonstrated that Prx I can preserve and promote the tumor-suppressive function of PTEN by preventing oxidation of PTEN under benign oxidative stress via direct interaction. Also, Prx II-deficient cells increased PTEN oxidation and insulin sensitivity. Furthermore, Prx III has been shown to protect PTEN from oxidation induced by 15s-HpETE and 12s-HpETE, these are potent inflammatory and pro-oxidant mediators. Understanding the tight connection between PTEN and Prxs is important for providing novel therapies. Herein, we summarized recent studies focusing on the relationship of Prxs and the redox regulation of PTEN.